Hábitos alimentarios y su relación con el estado nutricional de los preescolares de la Unidad Educativa Darío C. Guevara ubicada en la Parroquia El Salto Cantón Babahoyo mayo-septiembre 2019. - Sotomayor Morán, Jerly Stephany (2019)
Introduction: Currently, the inadequate feeding of children affects their nutritional status due to the high consumption of junk foods, processed foods and the lack of physical activity such as running dancing or playing. Objective: To determine the relationship between eating habits and the nutritional status of preschoolers of the Darío G Guevara Educational Unit located in the El Salto parish of the Babahoyo canton May – September 2019. Research methodology: The project was descriptive, applied in the field and cross-sectional with a quantitative approach. The sample was 50 preschoolers, the technique used for anthropometric measurements and which was compared with the WHO BMI / age percentiles and parents who they conducted a survey of the frequency and type of food their children consume to determine eating habits. Results: The results that were found in the investigation were 52% normal weight, 10% underweight, 30% show overweight and obesity 8%. The foods they consume most frequently are processed foods, fats, refined sugars that lead to malnutrition. Conclusions: in the study, eating habits were related to nutritional status and intrinsic relationship was found in the variables.